2021
DOI: 10.1093/nutrit/nuab061
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K – sources, physiological role, kinetics, deficiency, detection, therapeutic use, and toxicity

Abstract: Vitamin K is traditionally connected with blood coagulation, since it is needed for the posttranslational modification of 7 proteins involved in this cascade. However, it is also involved in the maturation of another 11 or 12 proteins that play different roles, encompassing in particular the modulation of the calcification of connective tissues. Since this process is physiologically needed in bones, but is pathological in arteries, a great deal of research has been devoted to finding a possible link between vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(92 citation statements)
references
References 205 publications
(327 reference statements)
2
85
0
5
Order By: Relevance
“…This enzyme catalyzes the attachment of carboxyl groups to Glu residues in proteins, whose carboxylation is vitamin K dependent [3,12,13]. This group consists of at least 18 proteins which include several proteins involved in blood clotting (protein C, S, M, Z, factors VII, IX, X and prothrombin), Gas6 (Growth Arrest-Specific 6 Protein), bone Gla protein (BGP or osteocalcin OC), matrix Gla protein (MGP), periostin and GRP (Gla Rich Protein) [6,7,[9][10][11][12][13]. The most important VKDPs are prothrombin, MGP and OC [6,7,10,11].…”
Section: Biological Role Of Vkmentioning
confidence: 99%
See 2 more Smart Citations
“…This enzyme catalyzes the attachment of carboxyl groups to Glu residues in proteins, whose carboxylation is vitamin K dependent [3,12,13]. This group consists of at least 18 proteins which include several proteins involved in blood clotting (protein C, S, M, Z, factors VII, IX, X and prothrombin), Gas6 (Growth Arrest-Specific 6 Protein), bone Gla protein (BGP or osteocalcin OC), matrix Gla protein (MGP), periostin and GRP (Gla Rich Protein) [6,7,[9][10][11][12][13]. The most important VKDPs are prothrombin, MGP and OC [6,7,10,11].…”
Section: Biological Role Of Vkmentioning
confidence: 99%
“…Vascular calcification is a dynamic process with the participation of calcification promoters and inhibitors and, at present, no particular therapy is known [2,11]. The mechanism of this process involves matrix-Gla protein (MGP), which is the most potent inhibitor of arterial calcification which belongs to Gla-containing proteins also known as Gla-rich protein GRP [1,3,4,7,11,13,16]. GRPs are dependent on vitamin K which is a cofactor of conversion of glutamate into Gla [1,3,16].…”
Section: Vitamin K Cardiovascular Risk and Vascular Calcificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Menadione, which is sometimes called vitamin K3, is another synthetic form of vitamin K. It was shown to damage hepatic cells, so it is no longer used in dietary supplements or fortified foods. Vitamin K shows very low toxicity levels also in the case of long-term supplementations [ 110 ]. Phylloquinone was used in combination with other vitamins or drugs for the treatment of primary mitochondrial disorders [ 63 , 111 , 112 , 113 ], although it cannot replace coenzyme Q10 in the mitochondrial respiratory chain of mammalian cells [ 114 ], despite what was observed in drosophila models [ 115 ].…”
Section: Small Molecules Vitamins and Cofactors Administered As Singl...mentioning
confidence: 99%
“…Advanced studies have revealed that PECSs containing the peptide synthetase-polyketide synthetase (PKS) island could induce DNA double-strand breaks in human cell lines, and thus, PECSs may be able to accelerate the development of colorectal cancer ( 12 14 ), which is a leading cause of cancer-related deaths worldwide ( 15 , 16 ). On the other hand, E. coli strains of groups A and D are not known to cause diseases and can even be beneficial to their hosts, e.g., by producing vitamin K 2 ( 5 , 17 , 18 ). Thus, the functions of these non-pathogenic E. coli strains (NPECSs) demand attention from researchers.…”
Section: Introductionmentioning
confidence: 99%